1997
DOI: 10.2175/106143097x125191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and pH on the kinetic growth of unialga Chlorella vulgaris cultures containing bacteria

Abstract: The kinetic growth of unialga Chlorella vulgaris was investigated in mixed-culture fed-batch chemos tat reactors, with special reference to temperature and pH. The experiments were carried out at looe to 40 o e, pH was controlled from 3.0 to 11.5 in a series of reactors, and glucose at a concentration of 75 mg/L was fed as the sole source of organic carbon. The maximum growth rate of 0.50 day-I was obtained at pH of about 6.31 to 6.84, and the optimum temperature was 32.4°e. The activation energy of the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(69 citation statements)
references
References 32 publications
5
61
0
3
Order By: Relevance
“…As it can be observed from Fig. 6, the kinetic model proposed by Mayo (1997) well describes the fact that each strain of microalgae has a relatively narrow optimal range of pH and most microalgal species are favored by neutral pH.…”
Section: Effects Of Phsupporting
confidence: 54%
See 3 more Smart Citations
“…As it can be observed from Fig. 6, the kinetic model proposed by Mayo (1997) well describes the fact that each strain of microalgae has a relatively narrow optimal range of pH and most microalgal species are favored by neutral pH.…”
Section: Effects Of Phsupporting
confidence: 54%
“…However, pH variation not only represents a fundamental indicator of the evolution of photosynthetic activity but can also, in turn, strongly affect the growth kinetics of microalgae influencing the distribution of carbon dioxide species and carbon availability thus causing direct physiological effects (Cornet et al 1995;Chen and Durbin 1994). Moreover, in microalgal cultures, the hydrogen ion is recognized to be a noncompetitive inhibitor near neutral conditions, while it can limit photosynthetic growth and substrate utilization rates at very low or very high pH levels (Mayo 1997). Furthermore, pH can affect the enzymatic activity of intra-and extracellular carbonic anhydrase, thus influencing the carbon capture mechanism of some microalgal strains (Concas et al 2012).…”
Section: Effects Of Phmentioning
confidence: 99%
See 2 more Smart Citations
“…Further increase in temperature (38 °C) led to an abrupt interruption of microalgal growth, and later the cells dead. The (20) found that the maximum growth rate was obtained at pH of about 6.31 to 6.84, and the optimum temperature was 32.4 °C. By (21) Ch.…”
Section: Effect Of Temperaturementioning
confidence: 98%